FREQUENCY OF CEREBRAL INFARCTION AND HAEMORRHAGE IN THE PATIENTS OF STROKE - ullah, Aman; Shah, Nazir; Rehman, Shams -ur-; Ataullah, Salma (Journal of Ayub Medical College Abbottabad, 2009)
Background: Stroke is rapidly developing phenomena of symptoms and signs of focal, and at times global, loss of cerebral function with no apparent cause other than that of vascular origin. The Objective was to know the frequency of cerebral infarction and haemorrhage in one hundred patients of stroke in a period of one year. Methods: Data was collected by consecutive sampling technique. Total one hundred patients of stroke were collected for the study. They were assessed through a detailed history of hypertension, diabetes mellitus, smoking, previous stroke, transient ischemic attack (TIA), previous myocardial infarction, angina, atrial fibrillation, alcohol intake, drugs used for hypertension/diabetes mellitus. Blood pressure was recorded at arrival and 24 hours after admission. Results: There were 70% males and 30% females. Twenty percent of the patients were in the age range of 51-60 years, 26% of the patients were in the age range of 61-70 years and 18% were in the age range of 71-80 years. Cerebral infarction was present in 72% patients while cerebral haemorrhage was present in 28% patients. Hypertension was the most common risk factor among these stroke patients. Average blood pressure was 180/100 mmHg. Conclusion: Cerebral infarction is the commonest form of stroke. Hypertension is the leading risk factor in stroke patients. Keywords: Cerebral Infarction, Cerebral haemorrhage, Hypertension, Stroke